2020
DOI: 10.1038/s41598-020-77392-5
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age is related to symptoms of attention-deficit/hyperactivity disorder in late-preterm to full-term children and adolescents with down syndrome

Abstract: Attention-deficit/hyperactivity disorder is frequently reported in individuals with Down syndrome, with considerable variation in the expression and severity of the symptoms. Despite growing evidence that gestational age predicts later symptoms of attention-deficit/hyperactivity disorder in the euploid population, this has not been studied in down syndrome. The current study is designed to investigate the influence of gestational age in later symptoms of attention-deficit/hyperactivity disorder in 105 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
(67 reference statements)
0
6
1
1
Order By: Relevance
“…These CHD-related findings stand in contrast to the null findings observed in the relationship between EF profile and other potentially relevant domains, such as premature birth, sex, CA, and composite biomedical and sensory impairment variables. Though previous research on infants with DS has demonstrated an association between cognitive dysregulation and premature birth [ 32 , 33 ], no meaningful association of this nature was observed in the present study. This may be attributed to the difference between direct observation measures versus proxy report data, or it may be the case that numerous other factors subsequent to the perinatal period exert a greater influence on the development of EF, such that these effects are no longer detectable between the ages of 3.00–10.99 years.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These CHD-related findings stand in contrast to the null findings observed in the relationship between EF profile and other potentially relevant domains, such as premature birth, sex, CA, and composite biomedical and sensory impairment variables. Though previous research on infants with DS has demonstrated an association between cognitive dysregulation and premature birth [ 32 , 33 ], no meaningful association of this nature was observed in the present study. This may be attributed to the difference between direct observation measures versus proxy report data, or it may be the case that numerous other factors subsequent to the perinatal period exert a greater influence on the development of EF, such that these effects are no longer detectable between the ages of 3.00–10.99 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Initial examinations of the association between CHD and developmental outcomes suggested an association with aspects of motor [ 26 ], cognitive, and language development [ 27 , 28 , 29 , 30 ]. A substantial number of infants with DS are born preterm [ 31 ], and this has recently been linked to attention regulation in infancy [ 32 ] and ADHD outcomes [ 33 ]. Other biomedical dimensions, such as vision and hearing impairments or history of significant illness, have not been examined for their longitudinal link to cognitive outcomes in DS.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence demonstrates that the occurrence of some of these ADHD symptoms are related to gestational age in both the TD and DS population, suggesting that ADHD symptoms are not simply inherent in DS (del Hoyo Soriano et al . 2020). Additionally, individuals with DS often have medical challenges that can impact attention and impulse control, including hypothyroidism, obstructive sleep apnoea, seizures and hearing and visual impairments, all of which contribute to the presentation of symptoms of inattention and hyperactivity and thus should be taken into considerations when assessing for, and differentially diagnosing, ADHD (Edvardson et al .…”
mentioning
confidence: 99%
“…In the case of DS, ID includes various cognitive domains, among which the impairment of visual, spatial, and verbal memory, language, and executive behaviors stand out as particularly severe [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. ID may be accompanied by psychiatric comorbidities, such as attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), mood disorders, psychosis, and regression [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Trisomy 21: Overviewmentioning
confidence: 99%
“…Intellectual disability (ID) present from infancy, however, is a constant hallmark of DS [4][5][6]. Although it exhibits a wide spectrum of severity, from very severe (IQ of [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] to mild (IQ of [3], it prevents a completely autonomous life. Moreover, people with DS are particularly prone to developing Alzheimer's disease (AD) starting from 35-40 years of age, which worsens an already compromised brain functioning because it leads to dementia [7].…”
Section: Trisomy 21: Overviewmentioning
confidence: 99%